Due postille a Demetrio Lacone (Pherc. 1012, col. XLVI 7-8 Puglia) e Filotimo (2 Steckerl) - Verde, Francesco (Rivista di Filologia e di Istruzione Classica, 2017)
Abstract In this short article I examine a passage from PHerc. 1012 including a work of the Epicurean philosopher Demetrius Lacon, and a testimony from Galen about the physician Phylotimus, a disciple of Praxagoras. As far as Demetrius’ text is concerned, I focus on the expression φό[βων | ὄντ]ων ἀδεήτων λόγων (col. XLVI 7-8 Puglia) in order to try to understand how the philosopher considers the phoboi to be alogoi. As for Galen’s passage (De usu partium, 3, 625, 1-2 Kühn = 2 Steckerl), I attempt to check whether Phylotimus’ view about the primacy of the heart compared with the brain is compatible with a scholium on the Iliad (Κ 10 = 1 Steckerl).